Protection of the lung from blast overpressure by stress wave decouplers, buffer plates or sandwich panels. Issue 1 (19th March 2018) - Sedman, Andrew; Hepper, A
Abstract : Introduction: This paper outlines aspects of UK Ministry of Defence's research and development of blast overpressure protection technologies appropriate for use in body armour, with the aim of both propagating new knowledge and updating existing information. Methods: Two simple models are introduced not only to focus the description of the mechanism by which the lungs can be protected, but also to provide a bridge between fields of research that may hold the key to further advances in protection technology and related body armour. Results: Protection can be provided to the lungs by decoupling the stress wave transmission into the thorax by managing the blast energy imparted through the protection system. Conclusions: It is proposed that the utility of the existing 'simple decoupler' blast overpressure protection is reviewed in light of recent developments in the treatment of those sustaining both overpressure and fragment injuries. It is anticipated that further advances in protection technology may be generated by those working in other fields on the analogous technologies of 'buffer plates' and 'sandwich panels'.